NIAT BELI ULANG KONSUMEN: KOMPETISI MARKETPLACE LOKAL DAN GLOBAL - Zalzalah, Guruh Ghifar; Gita Cahyati, Diana Indah; Basri, Anindita Imam (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2026)
The development of technology and the internet in the era of globalization has seen significant advancements, particularly in electronic commerce, which has become more sophisticated and widespread. A marketplace is an internet platform that serves as an intermediary between sellers and buyers for conducting transactions online. In Indonesia, there are two types of marketplaces: domestic and international. This study aims to examine the influence of hedonic and utilitarian values on consumers’ repurchase intention, mediated by attitude, using the Theory of Planned Behavior. This research adopts a quantitative approach, utilizing primary data collected through questionnaires. The sample was selected using a non-probability technique with purposive sampling, based on specific criteria: respondents aged 17 to 30 years who have made purchases on both domestic and international marketplaces and reside in Indonesia. The total number of respondents was 250. Data analysis using PLS-SEM with Smart PLS. This study demonstrates that hedonic and utilitarian values have a positive and significant influence on consumer attitudes and repurchase intention across both domestic and international marketplaces. Consumer attitude acts as a mediating variable, with full mediation occurring between hedonic value and repurchase intention, and partial mediation observed between utilitarian value and repurchase intention. These findings indicate that emotionally enjoyable experiences and perceived functional benefits can foster positive consumer attitudes, which in turn enhance repurchase intention in a sustainable manner.